Accelerometer-measured physical activity at 3 months as a predictor of symptoms of depression and anxiety 1 year after stroke: a multicentre prospective cohort study in central Norway - Ailan Phan; Torunn Askim; Stian Lydersen; Bent Indredavik; Torgeir Wethal (Journal of Rehabilitation Medicine, 2023)
Objectives: To study sedentary behaviour and physical activity at 3 months as predictors for symptoms of depression and anxiety at 1-year post-stroke.